2021
DOI: 10.1021/acs.est.1c04167
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of the Antibiotic Methylarsenite is Coupled to Denitrification in Anoxic Paddy Soil

Abstract: Arsenic (As) biomethylation is an important component of the As biogeochemical cycle, which produces methylarsenite [MAs(III)] as an intermediate product. Its high toxicity is used by some microbes as an antibiotic to kill off other microbes and gain a competitive advantage. Some aerobic microbes have evolved a detoxification mechanism to demethylate MAs(III) via the dioxygenase C−As lyase ArsI. How MAs(III) is demethylated under anoxic conditions is unclear. We found that nitrate addition to a flooded paddy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…in the enrichment cultures and M. thermophila were able to methylate arsenite to MMA but could not substantially further methylate MMA to DMA nor demethylate DMA or MMA, which is contrary to the observations in paddy soils, where methanogenic enrichment cultures were reported to demethylate methylated arsenic species. ,, MMA(III) was reported to be demethylated to inorganic arsenic by some microorganisms via a C–As bond lyase, ArsI, under aerobic conditions coupled to denitrification in anoxic paddy soils . To date, ArsI in methanogens has not been found yet, but Chen et al found that 13 C-DMA was partially transformed into 13 C–CH 4 in a methanogens-bearing experimental system .…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…in the enrichment cultures and M. thermophila were able to methylate arsenite to MMA but could not substantially further methylate MMA to DMA nor demethylate DMA or MMA, which is contrary to the observations in paddy soils, where methanogenic enrichment cultures were reported to demethylate methylated arsenic species. ,, MMA(III) was reported to be demethylated to inorganic arsenic by some microorganisms via a C–As bond lyase, ArsI, under aerobic conditions coupled to denitrification in anoxic paddy soils . To date, ArsI in methanogens has not been found yet, but Chen et al found that 13 C-DMA was partially transformed into 13 C–CH 4 in a methanogens-bearing experimental system .…”
Section: Discussioncontrasting
confidence: 62%
“…14,52,73 MMA(III) was reported to be demethylated to inorganic arsenic by some microorganisms via a C−As bond lyase, ArsI, under aerobic conditions 74 coupled to denitrification in anoxic paddy soils. 75 To date, ArsI in methanogens has not been found yet, but Chen et al found that 13 C-DMA was partially transformed into 13 C−CH 4 in a methanogens-bearing experimental system. 14 Demethylation of DMA occurring under methanogenic conditions was also observed by other authors.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculants were precultured to the mid-log phase before being introduced to the soil. Soil solution was collected at different time points during 15 days of incubation for the determination of As species [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Opposite to the process of As methylation, methylated As compounds can be demethylated by some microorganisms. It has been shown that MMAs(III) is demethylated by the dioxygenase C−As lyase ArsI in some bacteria [ 24 , 25 ]. DMAs can also be demethylated, although the mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%